A Comparative Study of Consumer Perception on the Usage of Cadbury Products in Malaysia and India - Rudresh Pandey; Ajay Massand; Suhasini BV; Lavi Sharma; Akansha Rai; Syazreen Aida; Daisy Mui Hung Kee; Rattanapoond Rattanapoond; Wan Syazwanie Syarina; Normaizatul Ilyana (AIBPM Publisher, 2021)
Chocolates and snacks are a humongous market all around the world. Mondelez International, the producer of Cadbury is a major player in this industry which perceives the Malaysian and Indian market differently. This study aims to examine the consumer perception on the usage of Cadbury products in Malaysia and India. The study would examine the association, usage, buying behavior and customer satisfaction in the two countries and identify similarities and differences among them. This study involves both primary and secondary data collected through various sources such as consumers from the two countries and publications. These findings provide a comparative insight about consumer perceptions about the products which help in understanding the two markets and marketing activities in detail.